Meningkatkan Kemampuan Komunikasi Matematika dengan Menggunakan Pendekatan Saintifik Pada Materi Kubus dan Balok - Mahmud, Irfan; Usman, Kartin; Takaendengan, Bertu (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2024)
This research aims to improve students' written mathematical communication skills through a scientific approach. Implementation of actions is carried out in two cycles. The subjects of this research were 22 students in class VIII of SMP NEGERI 6 SATAP Telaga Biru, consisting of 10 men and 12 women. The techniques used in this research were observation and tests. The data analysis techniques in this research are teacher observation, student observation, and mathematical communication tests. Research procedures include planning, implementation, observation, and reflection. The research consisted of 2 cycles. The results of the research show that there has been an increase in mathematical communication through scientific learning. This is shown by the research results that the scientific learning process has been running in accordance with the learning implementation plan and has succeeded in creating a conducive learning situation and improving mathematical communication. The results of the research showed that mathematical communication skills in cycle I were 55% poor criteria and in cycle II were 82% good criteria. The results of observations of teachers' teaching skills when managing learning has increased, in cycle I it reached 79.17% of good criteria, while in cycle II it reached 90.97% of very good criteria. The results of observations of student learning activities have increased, from cycle I the percentage was 70.63 good criteria, whereas in cycle II it was 82.5% very good criteria.